“Sistema de extracción de material particulado en la construcción del Hospital Regional Docente Ambato - Adriano Villa, Elena del Rocío (2016)
This research arises from the need to reduce absenteeism, caused for respiratory diseases that present the workers of the Army Corps of Engineers-Group Ambato. Workers are building Regional Teaching Hospital Ambato. Therefore the aim is to implement a system to remove particulate matter generated when executing tasks of cutting materials, for example: block, pavers and porcelain with the use of grinders, reducing occupational hazards for operators of this power tool as well as for the technical (supervisors, residents, superintendents, leaders and staff supervision) that involved in monitoring tasks. At the time of cutting materials like a block, pavers or porcelain generate particular material of size 2.5 or 10 microns. This is considered one of the main problems of pollution of the environment. So most people are affected, the danger to humans lies in the fact that fine particles are inhaled and travel directly through the respiratory tract, staying in the alveoli, bronchi and bronchioles lung, causing respiratory diseases. For example: Lung cancer (death). (Díaz V y Páez C, 2006) To determine the level of contamination in the workplace. Some people proceeded to monitor air quality, monitor parameters were: PM2.5 and PM10 of particulate matter, volatile organic compounds (COV`s), gases carbon monoxide (CO), sulfur dioxide (SO2) and nitrogen oxides (NO2), during activities cutting materials like a block, pavers and porcelain. The results of these analyzes showed that high levels of particulate matter. Also was elaborated a matrix identifying the risks that worker will have of the Ambato Military Group. Finally, with these data it was designed, built and implemented a computer that remove particulate matter; and checking the percentage reduction of pollutant when implementing the proposed extraction system in this investigation.